A Case Study on Energy Efficiency at Universiti Pertahanan Nasional Malaysia (UPNM) Building for Smart Campus Initiatives - Thanakodi, Suresh; Ismail, Nur Hidayah; Moh Nazar, Nazatul Shiema; Mukhtaruddin, Azharudin; Hidayat, Hendra; Mohd Isa, Mohd Rizal (JOIV : International Journal on Informatics Visualization, 2025)
In efforts to minimize harmful greenhouse gas (GHG) emissions and mitigate climate change, energy efficiency has become a global priority. Commercial buildings, including university facilities such as Universiti Pertahanan Nasional Malaysia (UPNM), play a significant role in this effort, particularly in becoming a smart campus. Commercial buildings have been identified as major contributors to greenhouse gas (GHG) emissions, primarily due to their high energy consumption for air conditioning, lighting, and other operational needs. In alignment with the Paris Agreement 2016, the Malaysian government has implemented various energy-saving initiatives to reduce carbon emissions and achieve Energy Efficient Building Star Ratings. This study analyses five years of energy consumption at UPNM using the desktop audit method. Data collected from January 2018 to December 2022 includes the Nett Floor Area (NFA), energy consumption, and maximum demand of the UPNM buildings. The analysis encompasses energy consumption and expenditure, maximum demand, Building Energy Intensity (BEI), carbon footprint, and building energy labeling under the National Building Energy Labelling Standard. The findings indicate that UPNM has achieved a 5-star rating in 2020 and 2021, compared to a 4-star rating in 2018, 2019, and 2022. The BEI of UPNM buildings from 2018 to 2022 met the Energy Commission (EC) requirement of being below 135 kWh/m²/year. This study has also identified recommendations for further enhancing the energy efficiency of the UPNM Building, including regular maintenance of electrical appliances and conducting energy efficiency awareness campaigns.